Pengaruh Kesantunan Berbahasa Guru Bimbingan Konseling Terhadap Efektifitas Penyelesaian Kasus Siswa di MTSN 2 Aceh Utara - Maulida; Yuhafliza, Yuhafliza (Aliterasi (Jurnal Pendidikan, Bahasa, dan sastra), 2023)
This research aims to explore and analyze the influence of language politeness used by Counseling Guidance (BK) teachers in communicating on the effectiveness of resolving student cases at MTsN 2 North Aceh. The research method uses a qualitative approach with a combination of interviews and observations, as well as a quantitative approach using a language politeness assessment scale questionnaire. Based on the results and discussion, the researcher can conclude: 1) The level of politeness in the language of Counseling Guidance (BK) teachers in handling cases among students at MTsN 2 Aceh Utara is good, this can be seen from the politeness scale obtained from questionnaire scores and the results of interviews with students MTsN 2 North Aceh. The data collected was 75% of the BK MTsN 2 North Aceh teachers using polite language both in terms of verbs and non-verbals. 2) The results of observations and interviews with MTsN 2 North Aceh students show that the influence of the use of polite language by Counseling Guidance teachers on the effectiveness of resolving student cases at MTsN 2 North Aceh reached 80%. This is shown by the resolution of several cases that have occurred, that students are increasingly rebellious, arrogant and even tend to be temperamental when judged with harsh words, shouted at, pushed into a corner, blamed without clear evidence or treated disrespectfully either with words or actions. Keywords: Language Politeness, Counseling Guidance Teachers, Student Cases